Reaksi Pasar Atas Peristiwa Pilpres 2014 - Oka Sudewa P., Dewa Gede; Ratna Sari, Maria M. (E-Jurnal Akuntansi, 2015)
This study is event study and aims to test whether or not the market reaction at the time of 2014 presidential election and around the date of implementation of the 2014 presidential election, which was measured using the normal return. The sample used is the companys incorporated in LQ45 period from February to July 2014. The period of observation that used is for 7 days. Analysis of data used one sample t-test and paired sample t-test. The results showed that no reaction to the market at the time of the presidential election in 2014 and theres absence of a difference in average abnormal return between before and after the 2014 presidential election.
Keywords: presidential election, abnormal return, event study